2016
DOI: 10.2298/hemind141106016r
|View full text |Cite
|
Sign up to set email alerts
|

Quality of fermented whey beverage with milk

Abstract: IzvodJedan od najekonomičnijih načina prerade surutke predstavlja proizvodnja napitaka kojom se u okviru samo jednog procesa iskorišćavaju svi potencijali surutke kao sirovine. Funkcionalne i senzorne karakteristike napitaka na bazi surutke su kriterijum koji je od presudnog značaja za plasiranje proizvoda na tržište i pridobijanje potrošača. Cilj ovog rada je bio određivanje nutritivnih i funkcionalnih karakteristika fermentisanog napitka od surutke i mleka dobijenog primenom komercijalne ABY-6 kulture. Rezul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…There are a large number of scientific reports that provide evidence of the health benefits of microorganisms including their production of antioxidants [22]. As shown in Table 1, during the fermentation process, the percentage of inhibition of DPPH radicals significantly (P < 0.05) increased from an initial value of 15.1% to variety of values recorded after the fermentation, just as expected on the basis of previous research [23,18] researchers [24] who found that the metabolic products of LAB obtained by utilization of oligosaccharides contribute to the higher antioxidant activity of yoghurt prepared by S. thermophilus, L. delbrueckii ssp. bulgaricus and L. plantarum.…”
Section: Viability and Leakingsupporting
confidence: 80%
“…There are a large number of scientific reports that provide evidence of the health benefits of microorganisms including their production of antioxidants [22]. As shown in Table 1, during the fermentation process, the percentage of inhibition of DPPH radicals significantly (P < 0.05) increased from an initial value of 15.1% to variety of values recorded after the fermentation, just as expected on the basis of previous research [23,18] researchers [24] who found that the metabolic products of LAB obtained by utilization of oligosaccharides contribute to the higher antioxidant activity of yoghurt prepared by S. thermophilus, L. delbrueckii ssp. bulgaricus and L. plantarum.…”
Section: Viability and Leakingsupporting
confidence: 80%
“…The concentration ranges were selected based on preliminary trials. Sucrose concentrations were chosen to reflect those usually found in commercial fermented beverages, and reported articles in which milk was added to the whey as a method for increasing the acceptability of fermented whey products [8,[22][23][24]. In this way, samples with different sensory characteristics were obtained, both in texture and flavour.…”
Section: Formulationsmentioning
confidence: 99%
“…In this sense, it is also interesting to use the previously demineralised sweet whey as an input for fermentation, to obtain a product with greater acceptability. To solve this drawback, some authors have produced fermented beverages from sweet whey with the addition of milk at different levels, significantly improving its aroma and flavour characteristics, thus causing an increase in the acceptability of the products [5][6][7][8]. In these articles, fermented beverages were made with a different degree of milk substitution with sweet whey.…”
Section: Introductionmentioning
confidence: 99%